Advances in Maltese linguistics - Saade, Benjamin; Tosco, Mauro (Studia Typologica, 2017)
This volume is a collection of up-to-date articles on Maltese on all linguistic levels, demonstrating the variety of topics Maltese has to offer for linguists of all specializations. Two diachronic studies discuss the early contact of Maltese and Sicilian Arabic (Avram) and the possible lexical influence of Occitan-Catalan on Maltese in the 13th-15th century (Biosca & Castellanos). Fabri & Borg shed light on the rules that govern verb sequences in Maltese. Čéplö presents a corpus analysis of the syntactic and semantic properties of focus constructions in Maltese. Stolz & Ahrens analyze the behavior of prepositional phrases with identical heads under coordination. Wilmsen & Al-Sayyed study the use of muš as a negator in Maltese and beyond. Puech presents a detailed phonological analysis of Maltese and Tunisian Arabic based on prosody, syllabic structure, and stress. Azzopardi-Alexander gives a fine-grained analysis of phonological features in Maltese English, placing speakers on a Maltese-English continuum. Sciriha takes a visual approach to multilingualism in Malta with her quantitative study of public and private signs. Finally, Versteegh offers a thought-provoking perspective on the notion "mixed language" and its viability